Assessments of the economic management and the action plan for the improvement of educational centres in the Valencian Community by the Education Inspectorate - Cerver Dasí, Mercé (Avances en Supervisión Educativa, 2023)
This article shows two external assessment plans for non-university educational institutions developed by the Education Inspectorate of the Valencian Community: the assessment and partial supervision of the financial management of public schools, as the core of their management autonomy, and the supervision and assessment of the action plan for the improvement, as the development of their pedagogical autonomy. From planning to the set of evaluation actions, we show as appendices the instruments used and refer to the URL of the Generalitat Valenciana’s Education Inspectorate to consult the regulatory documents that support them, as well as the models used. Each of these assessment plans has an executive report which is sent to the management team of the Regional Department responsible for Education and is made known to the school director.